EVALUATION OF STUDENT INTEREST AND TALENT DEVELOPMENT PROGRAM AT YASPORBI 1 ELEMENTARY SCHOOL - Hidayat, Annisa Zackyah; Zulaikha, Siti; Rochanah, Siti (International Education Trend Issues, 2023)
The purpose of this study was to evaluate the context, input, process, and product of the interest and talent development program for students at SD Yasporbi 1. The research method was descriptive qualitative. This type of research is the CIPP model evaluation research. The focus of this research is the interest and talent development program for students at SD Yasporbi 1. Data collection techniques used interviews, observation, and documentation studies. The results of the study show that (1) the context aspect is by the Extracurricular and P5 Technical Guidelines in Elementary Schools, namely the background of the extracurricular program, which is to facilitate and develop the potential, talents, and interests of students, as well as to grow the mentality and foster students' self-confidence. (2) The input aspect which includes planning, (3) The process aspect, the implementation of the extracurricular program includes program mechanisms, program implementation, management of infrastructure, manpower, and financing, (4) product aspect.